Pemanfaatan Media Kartu Gambar dalam Meningkatkan Kosakata Anak di PAUD Azzahroh Tebedak - Zaenal Abidin; Tri Rukmana; Dea Ananda; Novita Loka (Early Stage, 2026)
Early childhood is a golden age. Between the ages of 0-6, children experience rapid growth and development. However, some children experience developmental delays. This is influenced by several factors, such as the environment. This study aims to determine the benefits of picture cards in improving children's vocabulary. This study used a qualitative method with a field study approach. The research location was Azzahroh kindergarten in Tebedak, Ogan Ilir, South Sumatra. The subjects were children aged 4-5 years. Data collection techniques used were observation, interviews, and documentation. The data obtained was then analyzed using the Miles and Huberman approach, starting with data collection, data reduction, and drawing conclusions. The data was then tested for validity using source, technique and time triangulation. The results showed an increase in children's vocabulary skills after repeated learning activities using picture cards. At Azzahroh kindergarten, children's vocabulary development was in the Developing According to Expectations (BSH) category. Children found it easier to remember and pronounce new vocabulary, were able to name objects more clearly, and began to construct simple sentences in daily communication activities.